A participação popular na elaboração de políticas públicas de desenvolvimento local: um estudo no Município de Serrinha/RN (1997-2004) - Pena Júnior, Marcos Antonio Gomes (2007)
The question of participation has been debated in Brazil since the 1980 decade in search a better way to take care of poulation s demand. More specificaly after the democratic open (1985) begins to be thought ways to make population participates of decisions related to alocation of public resources. The characteristic of participates actualy doesn t exist, population to be carried through is, at top, consulted, and the fact population participates stays restrict to some technics interests at the projects, mainly of public politics of local development. Observe that this implementation happens through a process and that has its limits (pass) that could be surpassed through strategies made to that. This dissertation shows results of a research about participative practices in city of Serrinha between 1997 and 2004, showing through a study of the case of Serrinha what was the process used to carry through these pratices in a moment and local considered model of this application. The analyses were developed through a model of research elaborated by the author based on large literature respects the ideal process to implant a participative public politics. The present research had a qualitative boarding, being explorative and descritive nature. The researcher (author of this dissertation) carried through all the research phases, including the transcriptions of interviews that were recorded with a digital voice recorder. Before the analysis of these data was verified that despite the public manager (former-mayor) had had a real interest in implant a process of local development in city, he was not able to forsee the correct process to do it. Two high faults were made. The first was the intention to have as tool a development plan, what locked up to make this plan was the booster of supossed participative pratice and no the ideal model that would be a plan generate by popular initiative. The second one was absence of a critical education project for the population that should be the fisrt step to carry through a politc like that